2009
DOI: 10.1038/jcbfm.2008.157
|View full text |Cite
|
Sign up to set email alerts
|

Transient Focal Ischemia Induces Extensive Temporal Changes in Rat Cerebral MicroRNAome

Abstract: MicroRNAs (miRNAs) are ~22 nucleotides long, noncoding RNAs that control cellular function by either degrading mRNAs or arresting their translation. To understand their functional significance in ischemic pathophysiology, we profiled miRNAs in adult rat brain as a function of reperfusion time after transient middle cerebral artery occlusion. Of the 238 miRNAs evaluated, 8 showed increased and 12 showed decreased expression at least at 4 out of 5 reperfusion time points studied between 3 h and 3 days compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
369
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(393 citation statements)
references
References 43 publications
16
369
1
7
Order By: Relevance
“…The explanation for this is unclear, but is certainly one indicator of the gender-dependent differences of the immune response to IS. One or several epigenetic mechanisms might lead to the observed differences including DNA methylation or histone deacetylation (both of which suppress gene expression), DNA sumoylation, and microRNAs that generally downregulate expression of their many targets (Dharap et al, 2009;Liu et al, 2010). Future studies will be required to determine whether there are genderspecific modifications of DNA methylation, histone deacetylation, and/or microRNA responses after stroke.…”
Section: Gender-specific Gene Expression At Different Timesmentioning
confidence: 99%
“…The explanation for this is unclear, but is certainly one indicator of the gender-dependent differences of the immune response to IS. One or several epigenetic mechanisms might lead to the observed differences including DNA methylation or histone deacetylation (both of which suppress gene expression), DNA sumoylation, and microRNAs that generally downregulate expression of their many targets (Dharap et al, 2009;Liu et al, 2010). Future studies will be required to determine whether there are genderspecific modifications of DNA methylation, histone deacetylation, and/or microRNA responses after stroke.…”
Section: Gender-specific Gene Expression At Different Timesmentioning
confidence: 99%
“…26 In cerebral ischemic models, a few studies have profiled the broad miRNA changes in the ischemic brain and blood and provided novel mechanical insights and therapeutic targets. 6,7,27 In contrast, our study focused at the direct identification of neuroprotective miRNAs in the early IPC model at 3 hours after the brief ischemia and thus could suggest selective miRNAs involved in neuroprotection. Because our analysis used only cortical ischemic tissues influenced by IPC, our miRNA profiles were predesignated to the IPC study and the observed profiles in our ISC groups may be different from the previous observations that examined the entire ischemic hemisphere.…”
Section: Lee Et Al Micrornas In Ischemic Preconditioningmentioning
confidence: 99%
“…5 By analyzing the miRNA expression patterns in cerebral ischemia models, changes in miRNAs in cerebral ischemia have been revealed, 6 and antagonizing some of them was neuroprotective. 7 However, the analysis of IPC can reveal the miRNAs directly responsible for the neuroprotection. Thus, in this study, we investigated the miRNA profiles after IPC and associated neuroprotective mechanisms.…”
mentioning
confidence: 99%
“…These data suggest that miR-223 exerts a neuroprotective effect by regulating the expression and function of GluR2 and NR2B in stroke patients. A high expression of miR-145 is induced by stroke and superoxide dismutase-2 is one of the downstream targets (21). The knockdown of miR-145 increases the expression of superoxide dismutase-2, which may attenuate neuroprotection.…”
Section: Strokementioning
confidence: 99%